Cytosolic pH and the inflammatory microenvironment modulate cell death in human neutrophils after phagocytosis - Coakley, Raymond J.; Taggart, Clifford; McElvaney, Noel G.; O'Neill, Shane J. (Blood, 2002)
Following phagocytosis in vivo, acidification of extracellular pH (pHo) and intracellular metabolic acid generation contribute to cytosolic proton loading in neutrophils. Cytosolic pH (pHi) affects neutrophil function, although its regulation is incompletely understood. Its effect on mechanisms of neutrophil death is also uncertain. Thus, we investigated pHi regulation in Escherichia coli–exposed neutrophils, at various pathogen-to-phagocyte ratios (0:1-50:1), under conditions simulating the inflammatory milieu in vivo and correlated pHi changes with mechanisms of neutrophil death. Following phagocytosis, proton extrusion was dominated early by passive proton conductance channels, and later by Na+/H+ exchange (NHE). H+-translocating adenosine triphosphatase (V-ATPase) pHi regulation was evident primarily at lower bacterial densities. At physiologic pHo, lower pathogen-to-phagocyte ratios alkalinized pHi and inhibited apoptosis, whereas higher ratios acidified pHi (despite proton extrusive mechanisms) and promoted apoptosis. Necrosis was induced by high-density bacterial exposure at reduced pHo. Following phagocytosis, targeted inhibition of NHEs, proton conductance channels, or V-ATPases (amiloride, ZnCl2, or bafilomycin, respectively) moderately hyperacidified pHi and accelerated apoptosis. However, in combination they profoundly acidified pHi and induced necrosis. Proinflammatory mediators in vivo might affect both pHi regulation and cell death, so we tested the effects of bronchoalveolar lavage (BAL) fluid from patients with cystic fibrosis (CF) and healthy subjects. Only CF BAL fluid alkalinized pHi and suppressed apoptosis at physiologic pHo, but failed to prevent necrosis following phagocytosis at low pHo. Thus, a precarious balance between cytosolic proton loading and extrusion after phagocytosis dictates the mode of neutrophil cell death. pHi/pHo might be therapeutically targeted to limit neutrophil necrosis and protect host tissues during necrotizing infections.